PHARMACOKINETIC STUDIES DERIVED INDOLE SS-68 WITH ANTIARRHYTHMIC AND ANTIANGINAL PROPERTIES - Pavel Galenko-Yaroshevsky; Alexandr Kulikov; Dmitry Vinakov; Tatyana Avtina; Konstantin Suzdalev; Mikhail Pokrovskii (Belgorod National Research University, 2016)
A method of quantitative determination of SS-68 derivative of indole in rabbit blood plasma by high performance liquid chromatography with tandem mass spectrometric detector (HPLCMS/MS). Conducted pharmacokinetic studies SS-68 in the body of rabbits. Set the main pharmacokinetic parameters of the substance that allow you to optimize the future use of it's as a potential drug in cardiology practice.